Diagnostic accuracy of resting systolic toe pressure for diagnosis of peripheral arterial disease in people with and without diabetes: a cross‐sectional retrospective case‐control study - Peta Ellen Tehan; Alex Barwick; Mathew Sebastian; Vivienne Chuter (2017)
The resting systolic toe pressure (TP) is a measure of small arterial function in the periphery. TP is used in addition to the ankle-brachial index when screening for peripheral arterial disease (PAD) of the lower limb in those with diabetes, particularly in the presence of lower limb medial arterial calcification. It may be used as an adjunct assessment of lower limb vascular function and as a predictor of wound healing. The aim of this study was to determine the diagnostic accuracy of TP for detecting PAD in people with and without diabetes.